A 'boundary layer' finite element for thin multi-strake conical shells. (September 2018) - Boyez, Adrien; Sadowski, Adam J.; Izzuddin, Bassam A.
Abstract: Multi-strake cylindrical and conical shells of revolution are complex but commonplace industrial structures which are composed of multiple segments of varying wall thickness. They find application as tanks, silos, circular hollow sections, aerospace structures and wind turbine support towers, amongst others. The modelling of such structures with classical finite elements interpolated using low order polynomial shape functions presents a particular challenge, because many elements must be sacrificed solely in order to accurately represent the regions of local compatibility bending, so-called 'boundary layers', near shell boundaries, changes of wall thickness and at other discontinuities. Partitioning schemes must be applied to localise mesh refinement within the boundary layers and avoid excessive model runtimes, a particular concern in incremental nonlinear analyses of large models where matrix systems are handled repeatedly. In a previous paper, the authors introduced a novel axisymmetric cylindrical shell finite element that was enriched with transcendental shape functions to capture the bending boundary layer exactly, permitting significant economies in the element and degrees of freedom count, mesh design and model generation effort. One element is sufficient per wall strake. This paper extends this work to conical geometries, where axisymmetric elements enriched with Bessel functions accurately capture the bending boundary layer for both 'shallow' and 'steep' conical strakes, which are characterised by interacting and independent boundary layers, respectively. The bending shape functions are integrated numerically, with several integration schemes investigated for accuracy and efficiency. The potential of the element is illustrated through a stress analysis of a real 22-strake metal wind turbine support tower under self-weight. The work is part of a wider project to design a general three-dimensional 'boundary layer' element. Highlights: Conical shells exhibit boundary layer bending near discontinuities. Proposed element uses specialised bending shape functions to bypass mesh refinement. One element per strake yields accurate results in linear stress analysis examples. Conical boundary layer bending is characterised using two dimensionless parameters. Algorithm for efficient boundary layer meshing or plotting is also illustrated.